Agonist of inward rectifier K+ channels enhances the protection of ischemic postconditioning in isolated rat hearts. (July 2014) - Liao, Z; Feng, Z; Long, C
Background: Selective inhibition of inward rectifier K + channels could abolish the protection mediated by ischemic preconditioning, but the roles of these channels in ischemic postconditioning have not been well characterized. Our study aims to evaluate the effect of inward rectifier K + channels on the protection induced by ischemic postconditioning. Methods: Langendorff-perfused rat hearts (n=8 per group) were split into four groups: postconditioning hearts (IPO group); ischemic postconditioning with BaCl2 hearts (PB group); ischemic postconditioning with zacopride hearts (PZ group); and without ischemic postconditioning (CON group). After suffering 30 minutes of global ischemia, groups IPO, PB and PZ went through 10 seconds of ischemic postconditioning with three different perfusates: respectively, Krebs–Henseleit buffer (IPO group); 20 μmol/L BaCl2 (antagonist of the channel, PB group); 1 μmol/L zacopride (agonist of the channel, PZ group). Results: At the end of reperfusion, the myocardial performance was better preserved in the PZ group than the other three groups. The PB group showed no significant differences from the CON group. Conclusions: Our study has shown that the IK1 channel agonist zacopride is associated with the enhancement of ischemic postconditioning.